(untitled) (Balneo and PRM Research Journal, 2024)
Rehabilitation programs for patients with COPD are based on physical exercises usage, but accounting low tolerance to physical activity, this is not always a real task. The aim is to study the effect of haloaerosoltherapy (HAT) and complex rehabilitation treatment based on it on functional recovery of COPD patients. Materials and methods: 133 patients with COPD (GOLD II-III) beyond acute period were examined. Bronchial obstruction, intensity of clinical manifestations, disturbances of cardiovascular system were investigated. The 6-minute walk test was conducted. Results: Before treatment, it has been shown that exercise tolerance significantly depended on severity of bronchial obstruction, intensity of clinical manifestations and degree of cardiovascular risk. Treatment was carried out according to three treatment complexes (TC). TC-1 was based on HAT usage with certain concentration and dispersion of aerosol, 18-20 seances per course. In TC-2, singlet oxygen therapy was included, in TC-3 mineral water was administered as drinking use and inhalation. After course of treatment, walking distance covered in 6 minutes has been increased in patients of all groups. When using complex treatment, these changes were more pronounced. Conclusions: HAT with appropriate dispersion and concentration of haloaerosol promotes increasing tolerance to physical activity and may be used as a stage of physical rehabilitation with possible subsequent therapeutic physical exercises. Notably pronounced positive dynamics of studied data was noted in COPD patients convalescents after COVID-19.